Mongolia : Second Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Second Review Under the Stand-By Arrangement for Mongolia. All end-June performance criteria for the Second Review were met. The authorities have also implemented all but two of the end-June structural benchmarks, albeit with some delay. The creation of a screen-based system for interbank foreign exchange transactions has not been completed. However, the foreign exchange auction system established under the program is working well. The authorities' strong policy implementation under the program is working to stabilize market conditions and lower inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet